A multivariate statistical approaches on physicochemical characteristics of ground water in and around Nagapattinam district, Cauvery deltaic region of Tamil Nadu, India - Venkatramanan Senapathi (Earth Sciences Research Journal, 2013)
Ground water samples collected at different locations in and around the Nagapattinam district were analyzed for their physicochemical characteristics. The ground water samples were collected from fifty two dug and deep wells during the monsoon and summer seasons in June and December, 2011. The present investigation is focused on the determination of physico-chemical parameters such as pH, EC, TDS, Ca, Mg, Na, K, HCO3, SO4 and Cl. Ground water suitability for drinking, domestic and agri- cultural purposes was examined by using WHO standards. Correlation, factor and cluster analyses were applied to classify the ground water qualities and to categorize the geochemical processes controlling ground water geochemistry. Factor analysis indicates that seawater intrusion and agriculture runoff are dominant factors controlling the hydrogeochemistry of ground water in the study area. Cluster analysis was helpful for the classification on the basis of contamination characteristics of ground water quality. This study also elucidates that multivariate statistical analyses can be used to improve the understanding of ground water status and assessment of ground water quality.